The rationale for using low-molecular weight heparin in the therapy of symptomatic COVID-19 patients - Reichman-Warmusz Edyta; Warmusz Oliwia; Wojnicz Romuald (Open Medicine, 2022)
Accumulated evidence suggest that the adverse outcome of severe coronavirus disease 2019 (COVID-19) is closely related to prothrombotic microvascular pathology with a high risk of venous thromboembolism. Furthermore, the first observational studies indicated that adjunct therapy with low-molecular weight heparin (LMWH) was associated with lower mortality in this cohort of patients. However, the timing of starting LMWH and the dose remain controversial in COVID-19 patients. Considering the above, the aim of this study was to reveal the rationale for using LMWH in the therapy of symptomatic COVID-19 patients based on experimental and clinical studies on LMWH in inflammatory settings with special consideration given to randomized trials.